Psikologi pendidikan: suatu pendekatan baru - Muhibbin Syah (Remaja Rosdakarya, 1995)
ir,c.1-4,ws.c.5/ast c.6-7/oen, c.8/sgh c9/oen, c.10/ast c.11/c.12/sgh c13/ast c.14/ir,c.15,ws.c.16-17-24/ast c.25/ws.c.26-28/rt, c.21 ( kol hilang barcot sama /digtanti kol.revisi)/nr, .30-.32/irh,c.33-39